GATE PREPARATION BOT (International Journal of Food and Nutritional Sciences, 2024)
The GATE(graduate aptitude test) is one of the toughest exams in India. This project proposes the development of a chatbot, referred to here as the GATE Preparation Bot, to assist students in their exam preparation. The bot will leverage its digital format to provide students with a convenient and interactive learning experience.